Spline regression modelling of PTO performance of tractor fuelled with different biodiesels - Aybek, Ali; Arslan, Selcuk; Ucgul, Mustafa; Üçok, Serdar (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The objective of this study was to investigate the possibility of fitting spline regression models for power take-off (PTO) performance characteristics of an agricultural tractor tested with four different fuels, including diesel fuel (B0) and three biodiesel blends made of canola oil (B10: 10% biodiesel + 90% petro-diesel blend; B20: 20% biodiesel + 90% petro-diesel blend; B30: 30% biodiesel + 90% petro-diesel blend). The performance characteristics evaluated were PTO power, engine torque, engine fuel consumption, and specific fuel consumption. Due to sharp slopes in measured quantities around the nominal engine speed (2200 r/min), compared to the standard regression method, the spline regression models suited well to the experimental data with coefficient of determination R2=0.99 for PTO power and engine torque. R2 varied between 0.97 and 0.99 for fuel consumption and 0.91 and 0.95 for specific fuel consumption. The weaker correlation found for specific fuel consumption could be attributed to profound fluctuations in measured data causing atypical pattern in the corresponding graphs around the nominal engine speed. It was concluded that splines were useful to accurately predict the measured PTO power and engine torque. Neither standard methods nor splines were sufficient to obtain very good regression models for specific fuel consumption. Keywords: biodiesel, performance characteristics, power take-off, tractor, spline modelling DOI: 10.3965/j.ijabe.20171003.3220 Citation: Aybek A, Arslan S, Ucgul M, Üçok S. Spline regression modelling of PTO performance of tractor fuelled with different biodiesels. Int J Agric & Biol Eng, 2017; 10(3): 115–120.